Biotechnological Exploration of Transformed Root Culture for Value-Added Products. Issue 2 (February 2021) - Shi, Min; Liao, Pan; Nile, Shivraj Hariram; Georgiev, Milen I.; Kai, Guoyin
Abstract : Medicinal plants produce valuable secondary metabolites with anticancer, analgesic, anticholinergic or other activities, but low metabolite levels and limited available tissue restrict metabolite yields. Transformed root cultures, also called hairy roots, provide a feasible approach for producing valuable secondary metabolites. Various strategies have been used to enhance secondary metabolite production in hairy roots, including increasing substrate availability, regulating key biosynthetic genes, multigene engineering, combining genetic engineering and elicitation, using transcription factors (TFs), and introducing new genes. In this review, we focus on recent developments in hairy roots from medicinal plants, techniques to boost production of desired secondary metabolites, and the development of new technologies to study these metabolites. We also discuss recent trends, emerging applications, and future perspectives. Highlights: Hairy roots are useful tools for studying the biosynthesis of different plant-derived valuable compounds. Hairy roots could be preferred hosts when the desired compounds mainly accumulate in roots. Hairy roots are being considered as an alternative system to microbial hosts, including Escherichia coli and Saccharomyces cerevisiae, for producing plant-derived natural secondary metabolites because they are more similar to the native host plant. Hairy roots have emerged as valuable tools for the rapid characterization of plant gene function and enzyme activity in vivo because hairy roots naturally maintain many cofactors and precusor substrates, and the encoded plant-derived protein is more likely to be properly folded in hairy roots compared with in microbes.